AWS Lambda Quick Start Guide : Learn How to Build and Deploy Serverless Applications on AWS. - Klems, Markus (Packt Publishing Ltd, 2018)
Amazon Lambda is the part of Amazon Web Services that lets you run your code without provisioning or managing servers. Amazon Lambda is a compute service that enables you to deploy applications and back-end services that operate with zero upfront cost and require no system administration.